An Environmental quality control study on Astra Zeneca Pharmaceuticals (Phiippines), Inc. - Chung, Vincent Arnold; Jiao, Felise Isabel; Sarmiento, Wilburt (Diliman, Quezon City College of Engineering, 2004)
Astra Zeneca Pharmaceuticals (Philippines), Inc, a multi-national drug company has in the recent past experiencing problems in its environmental quality control system, specifically characterized by the frequent and recurring manifestation of out of specification points in its monitoring of air contamination levels. The group was therefore assigned, upon the onset of the project to address these concerns using concepts and tools in statistical quality control. Using past data provided by the company - data collected for the whole year of 2002 - the group executed failure mode analysis, control charting, capability and probability analysis and other problem solving tools to identify, analyze and address these problems. It was found that specific rooms in the production area were most susceptible to higher levels of contamination due to either unusually high manual activities or the nature of the process which take place in them, or both. Sixteen out of the more than thirty production rooms were identified to exhibit an air quality control system insufficient to meet the specification limits set by the company. These rooms had natural limits higher than those specified by the US FDA and cGMP standards. Their processes were declared out of control because their process capabilities, calculated using one-sided limits were either less than 1 or negative. This means that the processes' natural limits are wider that the acceptable and that the mean of the data points gathered is greater than the specification limit, respectively. While the air quality system of Astra Zeneca was concluded to be capable of delivering air within the specification limits, as displayed by the majority of the rooms whose capabilities were greater than one, the sixteen rooms which displayed unacceptable performance were concluded to need corrective action. Recommendations aimed to strengthen the air quality system, and an action-plan geared to address out of control conditions were made.
To address these weaknesses in the air system, three corrective measures were recommended: 1. An intensified physical cleaning system, and monitoring, 2. The use of supplementary air purifying equipment, 3. The use of a real time air monitoring system. While these recommendations are not mutually exclusive, it was suggested that an experimental study be conducted for a month to initially a few rooms to determine whether just the intensified cleaning procedures recommended would suffice considering its implementation involves very minimal costs. It was also recommended that simultaneous to this, few rooms to be subject also to the use of the new supplementary air purifying equipment and air monitoring software to be able to gauge the performance of both recommendations before full implementation. With an estimated total cost of Php116,160 for full implementation of the recommendations to the identified critical rooms, the probability of an alert of up to 55% would be reduced to 0.27%, with the natural limits falling within the specified alert limits, an improvement well worth the cost for a multinational drug company.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: Astra Zeneca Pharmaceutical Incorporated; Pharmaceutical industry; Quality control